Study of Different Porous Size MCM-41 Molecular Sieve as Carrier of Captopril - Li, Jing-Mei; Yu, Hui; Li, Xiao-Dong; Zhai, Qing-Zhou; Tian, Jian (Asian Journal of Chemistry, 2011)
In the study, two different porous size MCM-41 molecular sieves were synthesized by hydrothermal synthesis method under the different template and the prepared molecular sieves were used as the carrier of captopril drug. The structure of the prepared materials were characterized by powder X-ray diffraction, Fourier transform infrared spectra, nitrogen adsorption-desorption technique, transmission electron microscopy and scanning electron microscopy. The release process of the prepared drug was scouted in a simulated body fluid. During the drug release, it is found that the drug was rapidly released from the carrier during the first 1 h. After this, the release rate became comparative lentitude. For the (big-porous-MCM-41)-captopril sample (BC), the release rate was 50 % at 12 h and was 89 % at 36 h; for the (small-porous-MCM-41)- captopril sample (SC), it was 53 % at 5 h and was 99 % at 24 h.